Trade with China and skill upgrading: Evidence from Belgian firm level data - Giordano Mion; Hylke Vandenbussche; Linke Zhu (National Bank of Belgium, 2010)
We use Belgian firm-level data over the period 1996-2007 to analyze the impact of imports from China and other low-wage countries on firm growth, exit, and skill upgrading in manufacturing. For this purpose we use both industry-level and firm-level imports by country of origin and distinguish between firm-level outsourcing of final versus intermediate goods. Results indicate that, both industry-level import competition and firm-level outsourcing to China reduce firm employment growth and induce skill upgrading. In contrast, industry-level imports have no effect on Belgian firm survival, while firm-level outsourcing of finished goods to China even increased firm's probability of survival. In terms of skill upgrading, the effect of Chinese imports is large. Industry import competition from China accounts for 42% (20%) of the within firm increase in the share of skilled workers (non-production workers) in Belgian manufacturing over the period of our analysis, but these effects, as well as the employment reducing effect, remain mainly in low-tech industries. Firm-level outsourcing to China further accounts for a small but significant increase in the share of nonproduction workers. This change in employment structure is in line with predictions of offshoring models and Schott's (2008) 'moving up the quality ladder' story. All these results are robust to IV estimation
Keywords: F11; F14; F16; 330; import competition; outsourcing; China; skill upgrading; Internationaler Wettbewerb; Import; Outsourcing; Unternehmenserfolg; Humankapital; Qualifikation; Industrie; Belgien; China